2017
DOI: 10.1037/xhp0000425
|View full text |Cite
|
Sign up to set email alerts
|

Spelling ability selectively predicts the magnitude of disruption in unspaced text reading.

Abstract: We examined the effect of individual differences in written language proficiency on unspaced text reading in a large sample of skilled adult readers who were assessed on reading comprehension and spelling ability. Participants’ eye movements were recorded as they read sentences containing a low or high frequency target word, presented with standard interword spacing, or in one of three unsegmented text conditions that either preserved or eliminated word boundary information. The average data replicated previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 77 publications
7
22
1
Order By: Relevance
“…Nevertheless, it is important to note that (i) historically, Latin script was originally written without extra between-word spacing (scriptura continua; see Saenger, 1997), and (ii) many contemporary written languages such as Chinese, Japanese and Thai, do not use between-word spacing. Reading unspaced text is nevertheless harder than reading text with normal between-word spacing, a pattern revealed by a number of studies recording the eye movements of skilled readers while they read regularly spaced and unspaced text (Epelboim, Booth, Ashkenazy, Taleghani, & Steinman, 1997;Epelboim, Booth, & Steinman, 1994Morris, Rayner, & Pollatsek, 1990;Perea & Acha, 2009;Pollatsek & Rayner, 1982;Rayner, 1998;Rayner, Fischer, & Pollatsek, 1998;Spragins, Lefton, & Fisher, 1976;Veldre, Drieghe, & Andrews, 2017). 1 These studies have revealed that reading unspaced text is slower by about 40% to 70% than reading normally spaced text Rayner & Pollatsek, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is important to note that (i) historically, Latin script was originally written without extra between-word spacing (scriptura continua; see Saenger, 1997), and (ii) many contemporary written languages such as Chinese, Japanese and Thai, do not use between-word spacing. Reading unspaced text is nevertheless harder than reading text with normal between-word spacing, a pattern revealed by a number of studies recording the eye movements of skilled readers while they read regularly spaced and unspaced text (Epelboim, Booth, Ashkenazy, Taleghani, & Steinman, 1997;Epelboim, Booth, & Steinman, 1994Morris, Rayner, & Pollatsek, 1990;Perea & Acha, 2009;Pollatsek & Rayner, 1982;Rayner, 1998;Rayner, Fischer, & Pollatsek, 1998;Spragins, Lefton, & Fisher, 1976;Veldre, Drieghe, & Andrews, 2017). 1 These studies have revealed that reading unspaced text is slower by about 40% to 70% than reading normally spaced text Rayner & Pollatsek, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1 These studies have revealed that reading unspaced text is slower by about 40% to 70% than reading normally spaced text Rayner & Pollatsek, 1996). Readers make shorter saccades accompanied by longer fixations and more regressions when reading unspaced text, and the effect of word frequency on fixation durations is greater with unspaced text Veldre et al, 2017). Furthermore, given the overall shorter saccade lengths, initial landing positions are closer to the beginning of words in unspaced text (Paterson & Jordan, 2010;Perea & Acha, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…They observed the earliest discernible influence of word frequency in spaced text 112 ms from the start of fixation, with no discernible difference until 152 ms into the fixation when the text was unspaced. Finally, in an individual differences study, Veldre, Drieghe and Andrews (2017) observed that the negative impact of the unspaced format on reading behaviour was less pronounced for participants with good spelling ability, again linking the effects of spacing to lexical processing, more specifically to the quality of the lexical representations as indexed by spelling ability.…”
mentioning
confidence: 99%
“…Removing spaces in English results in an increase in reading times by 30-50% and it also increases average fixation durations, increases the number of fixations, increases the number of regressions, and reduces the average saccade length (Epelboim, Booth, Askenazy, Talghani & Steinman, 1997;Epelboim, Booth & Steinman, 1994; Malt & Seaman, 1978;McGowan, White, Jordan, & Paterson, 2014;Perea & Acha, 2009;Perea, Tejero & Winskel, 2015;Pollatsek & Rayner, 1982;Rayner, Fischer & Pollatsek, 1998;Rayner & Pollatsek, 1996;Sheridan, Rayner, & Reingold, 2013;Sheridan, Reichle & Reingold, 2016;Spragins, Lefton & Fisher, 1976;Veldre, Drieghe, & Andrews, 2017;Yang & McConkie, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation